A study on information wrapper protection profile - Farn, Kwo-Jean; Lin, Shu-Kuo; Hwang, Jiann-Ming (My University, 2007)
How to help the end-users to identify and analyze the attacks in cyberspace has become extremely important to the information security task. Based on the standard of the Information Security Audit and Alarms Framework published by ISO, in this paper we intend to investigate the security functional and security assurance requirements of the so-called Information Wrapper. Besides, in this paper we also propose a draft Protection Profile (PP) of Information Wrapper. The draft has been registered in the Chinese National Laboratory Accreditation (CNLA) as the security specification of relevant products and/or systems.
Keywords: common criteria (CC); protection profile (PP); information security audit and alarms; security assurance; security functional